Temperature Induced Aggregation and Clouding in Humic Acid Solutions. (8th February 2015) - Shaffer, Leah; von Wandruszka, Ray
Abstract : Humic acids in aqueous solution demonstrate inverse temperature-solubility relationships when solution conditions are manipulated to reduce coulombic repulsion among the humic polyanions. These effects were followed by dynamic light scattering (DLS) measurements of the resulting aggregates, as well as the addition of a polarity sensitive fluorescent probe (pyrene). The humic solutions could be primed for temperature induced clouding by carefully lowering the pH to a point where hydration effects became dominant. The exact value of the cloud point (CP) was a function of both pH and humate concentration. The CPs mostly lay in the range 50–90°C, but DLS showed that temperature induced aggregation proceeded from approximately 30°C onward. Similar effects could be achieved by adding multivalent cations at concentrations below those which cause spontaneous precipitation. The declouding of clouded humate solutions could be affected by lowering the temperature combined with mechanical agitation to disentangle the humic polymers.